Opportunities and Trade-offs among BECCS and the Food, Water, Energy, Biodiversity, and Social Systems Nexus at Regional Scales. (17th January 2018) - Stoy, Paul C; Ahmed, Selena; Jarchow, Meghann; Rashford, Benjamin; Swanson, David; Albeke, Shannon; Bromley, Gabriel; Brookshire, E N J; Dixon, Mark D; Haggerty, Julia; Miller, Perry; Peyton, Brent; et al.
Abstract: Carbon dioxide must be removed from the atmosphere to limit climate change to 2°C or less. The integrated assessment models used to develop climate policy acknowledge the need to implement net negative carbon emission strategies, including bioenergy with carbon capture and storage (BECCS), to meet global climate imperatives. The implications of BECCS for the food, water, energy, biodiversity, and social systems (FWEBS) nexus at regional scales, however, remain unclear. Here, we present an interdisciplinary research framework to examine the trade-offs as well as the opportunities among BECCS scenarios and FWEBS on regional scales using the Upper Missouri River Basin (UMRB) as a case study. We describe the physical, biological, and social attributes of the UMRB, and we use grassland bird populations as an example of how biodiversity is influenced by energy transitions, including BECCS. We then outline a "conservation" BECCS strategy that incorporates societal values and emphasizes biodiversity conservation.